Improving the sustainability of rice cultivation in central Thailand with biofertilizers and laser land leveling - Pame, Anny Ruth P.; Vithoonjit, Duangporn; Meesang, Nisa; Balingbing, Carlito; Gummert, Martin; Van Hung, Nguyen; Singleton, Grant R.; Stuart, Alexander M. (MDPI, 2023)
Rice production in the Central Plains of Thailand plays a key role in the country’s food security. However, the overuse of inputs coupled with the rising production costs are making it increasingly difficult for smallholder rice farming to remain economically and environmentally sustainable. Replicated production-scale field trials of Cost Reduction Operating Principles (CROP)—Thailand’s national package of best management practices for rice production—were established in tandem with laser land leveling (LLL), mechanical drum seeder, and the application of two biofertilizer products (i.e., PGPR II, that contains Azospirillum brasilense Sp. TS29 and Burkholderia vietnamiensis S45; and LDD #12, that contains Azotobacter tropicalis, Burkholderia unamae and Bacillus subtilis) and compared with farmer’s practices (FP). Performance indicators (PI) promoted by the Sustainable Rice Platform (SRP) were used to assess economic and environmental indicators. CROP + PGPR had significantly higher net income (79%) and nitrogen-use efficiency (57%) compared with FP. Pesticide use (28%), seed (60%), inorganic fertilizer N (41%) and total production costs (19%) were reduced in all CROP treatments compared with FP. These results demonstrate that the application of CROP, LLL, mechanical drum seeder, and biofertilizers can substantially improve the economic and environmental sustainability of rice production in the Central Plains of Thailand.